Safar'nāmah-'i Sayf al-Dawlah, ma'rūf bih Safar'nāmah-'i Makkah - Sayf al-Dawlah Sultān Muhammad, b. 1813 (Nashr-i Nay, 1985)
Account of the author's travels to several Arab countries and to some Iranian cities in 1862.